Genomic applications in horse breeding. (1st January 2016) - Stock, Kathrin F.; Jönsson, Lina; Ricard, Anne; Mark, Thomas
Abstract: New genomic tools for horses are adopted with some hesitance. This is in contrast with a considerable interest of owners and breeders in genome profiles of their horses, successful implementation of genomic selection in other species, and increasing awareness of the large prospects of using genomic data in horse breeding. Genomic applications in horses provide options for meeting the demand for introducing new traits in breeding. Limited availability of high quality phenotype data remains to be the major challenge, but improved prospects for breeding use can stimulate the systematic recording as it has already happened for equine health data. Given the importance of high quality phenotypes for genomic applications, recent initiatives for improving the routine data recording in horses in terms of objectivity of assessments, trait definitions, and coverage of functionality and health aspects may facilitate the development of genomically enhanced breeding programs. The desire to share costs and benefit the most from the use of equine genomic data in breeding is expected to stimulate further international collaboration across sport horse studbooks, highlighting the possible far-reaching impact and special facet of genomic selection as a new breeding tool also in horses.